1997
DOI: 10.1007/s00585-997-1123-x
|View full text |Cite
|
Sign up to set email alerts
|

An intercomparison between the GSWM, UARS, and ground based radar observations: a case-study in January 1993

Abstract: Abstract. The Global-Scale Wave Model (GSWM) is a steady-state two-dimensional linearized model capable of simulating the solar tides and planetary waves. In an e ort to understand the capabilities and limitations of the GSWM throughout the upper mesosphere and thermosphere a comparative analysis with observational data is presented. A majority of the observational data used in this study was collected during the World Day campaign which ran from 20 January to 30 January 1993. During this campaign data from 18… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
25
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 44 publications
1
25
0
Order By: Relevance
“…Regarding the tidal amplitudes, our simulation results show some agreement with certain observations in some disagreement with the GSWM-00, suggesting that the nonlinear effect could be an important cause of the discrepancy between the observation and the GSWM-00. Palo et al (1997) provided a comparison between the GSWM, UARS, and ground-based radar observations in January 1993, and found that there were a number of cases where their agreement was not particularly good between 95 and 105 km. One such instance is for the meridional semidiurnal tide in the Northern Hemisphere, where the GSWM estimates may exceed observations by 50%.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Regarding the tidal amplitudes, our simulation results show some agreement with certain observations in some disagreement with the GSWM-00, suggesting that the nonlinear effect could be an important cause of the discrepancy between the observation and the GSWM-00. Palo et al (1997) provided a comparison between the GSWM, UARS, and ground-based radar observations in January 1993, and found that there were a number of cases where their agreement was not particularly good between 95 and 105 km. One such instance is for the meridional semidiurnal tide in the Northern Hemisphere, where the GSWM estimates may exceed observations by 50%.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that in the MLT, large tidal amplitude may lead to many nonlinear effects, which cannot be described appropriately by the linearized GSWMs. In fact, a number of tidal observations in different latitudinal regions (Burrage et al, 1995;Palo et al, 1997;Oberheide et al, 2000;Bruinsma et al, 2002;Grieger et al, 2002;Pancheva et al, 2002;She et al, 2003;Batista et al, 2004; showed obvious discrepancies from the GSWMs, especially at altitudes above 90 km, where larger tidal amplitudes appear and have the potential to lead to a stronger nonlinear interaction. The effect of the nonlinear interaction is not clear and needs to be investigated.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…These instruments provided a powerful global view of the wind field of the planet. In addition to studying MLT region atmospheric dynamics, they also provided the means and motivation for the intercomparison of MLT winds derived from different techniques for the purposes of ground proofing the satellite measurements (e.g., Palo et al 1997), and provided a better understanding of the limitations of the various measurement techniques.…”
Section: Satellite Intercomparisonsmentioning
confidence: 99%